PERPUSTAKAAN UMUM BERBASIS INKLUSI SOSIAL: APA DAN BAGAIMANA PENERAPANNYA? (SEBUAH KAJIAN LITERATUR) - Reza Mahdi (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Ilmu Budaya, UIN Sunan Kalijaga Yogyaka, 2020)
If we look at the definition of a public library itself, namely a library that is used as a means of lifelong learning regardless of gender, physical condition, race, ethnicity, religion, social and economic status. That means the concept of social inclusion is very suitable to be implemented in the library. The latest public library paradigm is as a vehicle for people to develop their potential so that it leads to an increase in living standards. Regarding the concept of social inclusion, of course, it has a relationship with public libraries because they both talk about equality. Social inclusion means efforts to make society open to one another, especially to vulnerable or potentially marginalized communities, one of which is through community empowerment activities. This research is a qualitative study using the literature study method, namely collecting and analyzing the literature as a data source. To check the validity of the data, data source triangulation was carried out by looking for other data to strengthen the previous data. In this study, it was found that a public library based on social inclusion means a public library that always guarantees its facilities and services in order to encourage people to be open to one another. Several things that need to be considered in building a public library based on social inclusion, namely (1) the existence of community empowerment activities, and (2) the right to get library services, and (3) the accessibility of library information. Therefore it can be concluded that public libraries are closely related to the concept of social inclusion so that they can apply the concept. Of course, this can be seen from the public library itself which has the character of protecting all levels of society without a reed perspective.